"Unicorn humour isn't very subtle." Graphic novels and comics as a potential didactic tool for teaching irony to children: the example of Dana Simpson's Phoebe and her unicorn. Issue 2 (4th March 2022) - Banasik-Jemielniak, Natalia
ABSTRACT: Children find verbal irony difficult to understand. Yet they need to acquire the skill of comprehending it in order to become proficient communicators and to master deep reading. Graphic novels and comics can expose children to non-literal expressions, including verbal irony. In the paper, I argue that graphic novels and comics may be used as a powerful tool for teaching irony to children, using Phoebe and her Unicorn by Dana Simpson as an example of a literary source of children's exposure to ironic language. While I analyse chosen instances of irony used in the comic, I postulate that in consideration of recent studies on figurative language comprehension, irony should be taught to children.